Studi Komunitas Ikan Karang pada Struktur Buatan yang Berbeda di Perairan Tanjung Benoa, Kabupaten Badung, Bali - Lyndale, Dawson; Wiyanto, Dwi Budi; Atmaja, Putu Satya Pratama; Hukom, Frensly Demianus (Bumi Lestari; Vol 25 No 1 (2025)DO - 10.24843//blje.2025.v25.i01.p05, 2025)
In an effort to address coral reef degradation, several methods have been employed to rehabilitate these ecosystems, including the creation and development of artificial reefs. Coral fish can serve as indicators of the success of these artificial reef structures, with the hope that natural coral reef ecosystems can grow undisturbed and recover. This research was conducted from May to December 2021 and May to December 2022, using the Underwater Visual Census (UVC) method to assess the diversity and biomass of coral fish from eight families, namely Chaetodontidae, Acanthuridae, Scaridae, Siganidae, Haemulidae, Lutjanidae, Lethrinidae, and Serranidae. At six observation sites in the waters of Tanjung Benoa, Badung Regency, Bali, different structures were found, including spider structures, concrete structures, statues, table racks, biorock structures, and roti buaya structures. Based on the research findings, the species diversity index of coral reef fish at each location ranged from low to high. The total biomass of coral fish overall ranged from 0.66 kg/ha to 7.84 kg/ha. Correspondence analysis revealed a relationship between several species and the observed structures at each location. This indicates that the ICRG project has successfully attracted fish populations, making it suitable for dive sites in the Badung regency, Bali.